2010
DOI: 10.1111/j.1469-7580.2010.01231.x
|View full text |Cite
|
Sign up to set email alerts
|

When cortical development goes wrong: schizophrenia as a neurodevelopmental disease of microcircuits

Abstract: Schizophrenia probably has a developmental origin. This review refers to three of our published series of studies related to this hypothesis: loss of dendritic spines on cerebral neocortical pyramidal neurons, decreased numerical density of glutamatergic neurons, and microgliosis. First, brains of schizophrenic patients and nonschizophrenic controls were obtained post mortem and blocks of multiple cortical areas impregnated with a Rapid Golgi method. Spines were counted on the dendrites of pyramidal neurons of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
102
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(110 citation statements)
references
References 70 publications
(62 reference statements)
5
102
0
3
Order By: Relevance
“…Reductions in neuron density in the primary visual cortex (Dorph-Petersen et al, 2007) and reduced glutamatergic neurons in the orbitofrontal cortex have been reported (Garey, 2010). Presently, the DISC1 status of the patients reported in those studies is unknown.…”
Section: Discussionmentioning
confidence: 85%
“…Reductions in neuron density in the primary visual cortex (Dorph-Petersen et al, 2007) and reduced glutamatergic neurons in the orbitofrontal cortex have been reported (Garey, 2010). Presently, the DISC1 status of the patients reported in those studies is unknown.…”
Section: Discussionmentioning
confidence: 85%
“…Not all of the molecular changes observed in hippocampi of schizophrenia patients have been detected in the MAM rats (Eastwood et al, 1995a;Eastwood and Harrison, 1998;Fatemi et al, 2000), although the same pathways and cellular functions were found to be affected, as identified by in silico pathway analysis and supported by TAC analysis. Such molecular changes may result from a decreased number of total synapses, defective synaptic coupling, or a change in the neuropil formation, as suggested by Matricon et al (2010) for the MAM-E17 model and demonstrated in cases of human schizophrenia subjects (Garey, 2010).…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, the origin of these changes in the hippocampus is unclear. LC-MS E profiling of whole hippocampal tissue as used here does not take into account cell morphological and subfield-specific expression differences as seen in schizophrenia studies (Benes et al, 1991;Eastwood et al, 1995b;Gao et al, 2000;Garey, 2010;Knable et al, 2004). Therefore, we suggest that future studies should investigate subcellular and subregional expression and phophorylation patterns of synaptic markers and glutamatergic indices, as identified in this study, in combination with synaptic structure and density measurements in hippocampal subfields of the MAM-E17 rat model.…”
Section: Future Directions and Conclusionmentioning
confidence: 96%
“…In the past two decades, several studies have described cytoarchitectural and neuronal morphometric abnormalities consistent with defects in early neurodevelopment at the level of the PFC, particularly in the left hemisphere (Kalus et al, 2000;Garey, 2010;Yang et al, 2011). In schizophrenia, miswiring of neuronal connections due at least in some cases to neurodevelopmental failures would result in disconnectivity between different integrative brain regions, especially the PFC, temporal lobe, and striatal regions (Lawrie et al, 2002;Stephan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%